Approximately one‐half of patients with early‐stage hepatocellular carcinoma meeting Milan criteria did not receive local tumor destructive or curative surgery in the post‐MELD exception era. Issue 11 (3rd March 2014) - Devaki, Pardha; Wong, Robert J.; Marupakula, Vidyasagargoud; Nangia, Sharad; Nguyen, Long; Ditah, Ivo C.; Ehrinpreis, Murray N.; Nguyen, Mindie H.
Abstract : BACKGROUND: Since 2002, priority Model for End‐stage Liver Disease (MELD) exception status has been given to patients with hepatocellular carcinoma (HCC) who meet the Milan criteria. Since then, the number of liver transplantations performed in patients with HCC has increased, but to the authors' knowledge, few studies to date have examined the effect of MELD exception recommendations on therapy use and survival rates in a nationwide sample. The current study examines therapy use and long‐term survival rates among patients with HCC tumors meeting the Milan criteria in the post‐MELD exception era. METHODS: The current study is a retrospective cohort study of 2179 patients with localized HCC meeting the Milan criteria who were registered between 2004 and 2007 in the Surveillance, Epidemiology, and End Results database. RESULTS: A total of 43% of patients did not receive any specific therapy. Overall, the 5‐year relative survival rate for patients receiving only supportive care was dismal at 24% (95% confidence interval [95% CI], 21%‐27%), whereas that for patients undergoing liver transplantation was 77% (95% CI, 71%‐82%). Long‐term survival was found to be dependent on age, race/ethnicity, and type of therapy received. A multivariate Cox proportional hazards model adjusted for age, race/ethnicity, and type of therapy received demonstrated that, compared with white patients, black patients had significantly poorer survival outcomes (hazards ratio, 1.23; 95% CI, 1.03‐1.47 [ P  = .02]), whereas Asian/Pacific Islander patients had significantly better survival rates when compared with white patients (HR, 0.66; 95% CI, 0.57‐0.77 [ P  < .001]). CONCLUSIONS: Despite having localized disease that met transplantation criteria, nearly 50% of the large nationwide cohort of patients with HCC in the current study received only supportive care and had dismal 5‐year relative survival rates, especially among black patients. Cancer 2014;120:1725–1732 . © 2014 American Cancer Society . Abstract : Despite meeting the criteria for liver transplantation, nearly one‐half of eligible patients with localized hepatocellular carcinoma did not receive any therapy. Even in this current era, racial disparities in long‐term survival exist, with black patients found to have the worst survival.